An Analysis of The Main Character on A Novel Titled “It Happened One Summer” by Tessa Bailey - Alicia Giselle Jeanneta Gow; Friska Dita (BLESS, 2026)
This study analyses the character development of Piper Bellinger in a book titled It Happened One Summer by Tessa Bailey. This research focuses on Piper’s character development after getting send to Westport as a punishment from making a scene, using Freud’s (2010) psychoanalysis. Using qualitative approach, data were collected by writing down things related to the character. Freud (2010) characterized id, ego, and superego as components of human psychology. These components play a big role in understanding character development. The analysis discovers two points about Piper Bellinger. At the beginning of the story, Piper’s id drives her, and the id is the cause of her immature and impulsive acts. She does anything to be famous, and she has no dream to pursue. After being sent to Westport, Bellinger then changes and is driven by her superego, which considers everything based on moral values. She realized that fame is hollow and loveless.